A new Oriental genus of Deltocephalinae (Hemiptera: Cicadellidae) from China and Thailand - Dai, Wu; Zhang, Yalin (Zootaxa, 2011)
A new deltocephaline leafhopper genus Hamulotettix is described and illustrated based on a large, distinctly patterned species, Hamulotettix ungulatus sp. nov., from China and Thailand, and is tentatively placed in the tribe Athysanini. Detailed morphological description and illustrations are provided. The genus is similar to Abrus Dai & Zhang in external body form, and also bears a superficial resemblance to Oxycephalotettix Zahniser, in having segment X of the male abdomen with a falcate ventral process.